Comparison of the Efficacy and Tolerability of Dienogest and Dienogest Plus Ethinylestradiol on Endometriosis Related-Pain - Tolga Karacan; Huseyin Kiyak; Eser Ozyurek; Mevlide San; Engin Oral (Gynecology Obstetrics & Reproductive Medicine)
Objective: Endometriosis is a common gynecological condition that affects many women of reproductive age worldwide and is a major cause of pain and infertility. Treatment of endometriosis can be either surgical, aiming to restore normal anatomy by removing endometriotic lesions, or hormonal. Various medical treatments with different doses, formulations, delivery systems, and regimens have been tested. The main objective of this study was to compare the efficacy and tolerability of dienogest and dienogest plus ethinylestradiol on endometriosis-related pain. Additionally, the effects on endometrioma size were examined.